Prediction of fracture and damage in micro/nano coating systems using cohesive zone elements. (15th August 2017) - Rezaei, Shahed; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: For reasons of wear resistance and better performance, manufacturing tools are frequently applied with coatings. Such coatings should be made of materials with satisfactory lifetime and degradation resistance. By using the cohesive zone (CZ) element technique embedded at grain boundaries as well as in the interface between the coating and the substrate, a numerical model is developed which serves to predict the damage behavior and crack propagation in the coating system. Different numerical treatments are tested to improve the convergence of the CZ modeling. The present numerical studies reveal the most effective parameters in order to produce stronger coatings. These parameters can be summarized as: grain morphology, elastic and plastic properties, residual stresses and the form of the traction-separation law for the cohesive zone model.